Removal of Yellow ME 7 GL from industrial effluent using electrochemical and adsorption techniques. (17th November 2010) - Mittal, Alok; Jain, Rajiv; Mittal, Jyoti; Varshney, Shaily; , Shalini Sikarwar
Attempts have been made to remove toxic dye Yellow ME7GL using electrochemical and adsorption techniques. Both techniques are capable of reducing toxicity and producing clean water for reuse. The electrochemical removal is carried out at platinum electrode and cyclic voltammograms of the dye solutions have been recorded at different pH, concentrations, scan rates, etc. The adsorption of the dye has been carried out over activated charcoal and wheat husk and verified by Langmuir and Freundlich adsorption isotherms. The decolouration of the dye was also examined by monitoring the Chemical Oxygen Demand (COD) of the untreated and treated dye solutions.